Analysis of the use of sodium bicarbonate for the performance of surfing athletes - Hanada, T. Z. B.; Knack, R.; Mayr, K.; Knack, R. S.; Guedes, D.; Scorcine, C.; Pereira, R. (Qeios, 2023)
Purpose: Surfing is a sport in which the intensity and duration of training varies. Therefore, strategies that contribute to muscle attenuation may be efficient to improve surfers' performance. Objective: The aim of this study was to investigate the effectiveness of sodium bicarbonate on surfers' performance.